1988
DOI: 10.1080/00365599.1988.11690392
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drainage Conditions on Mucosal Bladder Damage By Indwelling Catheters: II. Histological Study

Abstract: A previous study demonstrated a strong but short-lasting suction through the catheter eyes by a hydro-dynamically generated negative pressure fluctuation terminating bladder evacuation in some frequently occurring circumstances of indwelling catheter drainage. This report regards the biological effect. Fifteen successive evacuations on such drainage conditions in each of 4 anesthetized pigs were followed by cystectomy and histological examination. All bladders presented small swollen areas, histologically show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 11 publications
2
26
1
Order By: Relevance
“…It has been demonstrated that human urinary catheterization causes histological and immunological changes in the bladder due to mechanical stress that results in a robust inflammatory response, exfoliation, edema of the lamina propria and submucusa, urothelial thinning, and mucosal lesion of the urothelium and kidney 35,36 . Additionally, the catheter provides a surface for bacterial attachment thereby creating an environment utilized by several species to cause CAUTI.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that human urinary catheterization causes histological and immunological changes in the bladder due to mechanical stress that results in a robust inflammatory response, exfoliation, edema of the lamina propria and submucusa, urothelial thinning, and mucosal lesion of the urothelium and kidney 35,36 . Additionally, the catheter provides a surface for bacterial attachment thereby creating an environment utilized by several species to cause CAUTI.…”
Section: Introductionmentioning
confidence: 99%
“…Local mechanical trauma and chronic irritation of the bladder epithelium from indwelling catheters, like schistosomiasis, are believed to promote the development of bladder cancer due to the induction of epithelial hyperplasia [8]. This trauma can be due to pressure damage from the catheter tip as the bladder drains and collapses around the catheter or from suction damage as the bladder wall is aspirated into the drainage eyelets [9][10][11]. Not only does this constant irritation promote a much localized chronic inflammatory response, but the mechanical trauma associated with long-term catheterization has been demonstrated to create alterations in histological architecture hypothesized to provide a route for both local spread and distant metastasis [8,12].…”
Section: Discussionmentioning
confidence: 99%
“…Another issue arises from the media itself, it was discovered that in mice and humans, urinary catheterization causes physical trauma to the lining of the bladder, inducing an inflammatory response and consequently, changing the bladder environment [66,125,[163][164][165][166]. As part of the inflammatory response, serum proteins are released and accumulated into the bladder and deposited onto the urinary catheter [64][65][66]150,167].…”
Section: Inconsistencies In Testing New Coatingsmentioning
confidence: 99%